Nucleobase-modified nucleosides and nucleotides: Applications in biochemistry, synthetic biology, and drug discovery - Berdis, Anthony (Frontiers in Chemistry, 2022)
Abstract. DNA is often referred to as the “molecule of life” since it contains the genetic blueprint for all forms of life on this planet. The core building blocks composing DNA are deoxynucleotides. While the deoxyribose sugar and phosphate group are ubiquitous, it is the composition and spatial arrangement of the four natural nucleobases, adenine (A), cytosine (C), guanine (G), and thymine (T), that provide diversity in the coding information present in DNA. The ability of DNA to function as the genetic blueprint has historically been attributed to the formation of proper hydrogen bonding interactions made between complementary nucleobases. However, recent chemical and biochemical studies using nucleobase-modified nucleotides that contain “non-hydrogen bonding” functional groups have challenged many of the dogmatic views for the necessity of hydrogen-bonding interactions for DNA stability and function. Based on years of exciting research, this area has expanded tremendously and is thus too expansive to provide a comprehensive review on the topic. As such, this review article provides an opinion highlighting how nucleobase-modified nucleotides are being applied in diverse biomedical fields, focusing on three exciting areas of research. The first section addresses how these analogs are used as mechanistic probes for DNA polymerase activity and fidelity during replication. This section outlines the synthetic logic and medicinal chemistry approaches used to replace hydrogen-bonding functional groups to examine the contributions of shape/size, nucleobase hydrophobicity, and pi-electron interactions. The second section extends these mechanistic studies to provide insight into how nucleobase-modified nucleosides are used in synthetic biology. One example is through expansion of the genetic code in which changing the composition of DNA makes it possible to site-specifically incorporate unnatural amino acids bearing unique functional groups into enzymes and receptors. The final section describes results of pre-clinical studies using nucleobase-modified nucleosides as potential therapeutic agents against diseases such as cancer.